Investigation of different configurations for single and double spacing multi-wavelength brillouin-raman fiber laser - Mamdoohi, Ghazaleh (2014)
The work in this thesis focuses on generation of multi-wavelength Brillouin-Raman fiber laser (MBRFL) with single and double frequency Brillouin spacing shift. Three main configurations have been proposed to accomplish this aim. These are achieved based on the stimulated Brillouin scattering (SBS), stimulated Raman scattering (SRS), and stimulated Rayleigh scattering (SRLS). In all architectures, dispersion compensating fiber (DCF) is utilized as a nonlinear Brillouin-Raman gain medium. Firstly, a new MBRFL utilizing enhanced nonlinear amplifying fiber loop (NAFL) design is proposed and demonstrated to produce adjustable 10 and 20 GHz wavelength spacing. We developed a detailed theoretical analysis, which represents a good foundation on which operation of MBRFL with 10 and 20 GHz spacing is satisfied. By proper adjustments of splitting ratio, the wavelength interval can be adjusted, thus improving the laser performance. Utilizing 50/50 coupler offers 443 flat amplitude channels with 10 GHz spacing and 16.5 dB average Stokes optical signal-to-noise ratio (S-OSNR). On the other hand, 1/99 coupler is desirable for multiple Stokes combs with 20 GHz spacing in which 221 lasing lines with an average 25 dB S-OSNR are generated. The employment of a mirror at the end of this cavity, which is dubbed as the nonlinear amplifying loop mirror (NALM) design is responsible for initiation of lower threshold for SBS effect that leads to the excellent results. A total of 28 channels with 10 GHz spacing and an average 17 dB S-OSNR are achieved when the Raman pump power (RPP) is fixed at only 300 mW. This is the most efficient 10 GHz MBRFL reported at very low RPP through a simple configuration. The second configuration is proposed to generate a MBRFL with 20 GHz spacing via forward pumping scheme. The setup is arranged in a linear cavity by employing 7.2 and 11 km DCF in addition to a 30 cm Bismuth oxide erbiumdoped fiber (Bi-EDF). It is found that incorporating 11 km DCF with Bi-EDF results in multiple Brillouin Stokes signals with outstanding OSNR. In this case, a total of 186 Brillouin Stokes combs with -13.5 dBm Stokes peak power (SPP) and an average 28 dB S-OSNR are produced. These results are achieved when Brillouin pump (BP) power of -2.6 dBm , BP wavelength of 1545 nm , and RPP of 900 mW are injected into the cavity. However, characteristics improvement of MBRFL with 20 GHz spacing in terms of channels count, SPP, and wavelength operation is another aim of this work which is successfully accomplished by introducing the third configuration. In this structure, incorporation of Raman pump source with a set of couplers with various ratios leads to different Brillouin Stokes lines features. The optimization of multi-wavelength laser operation is done with proper adjustments of coupling ratio, BP wavelength, BP power, and RPP. The results demonstrate that the best S-OSNR performance is satisfied at coupling ratio of 50/50. When setting the RPP to 1000 mW, 212 flat amplitude Stokes lines with -10 dBm SPP and an average 27.5 dB S-OSNR are achieved. In this case, the BP power and its corresponding wavelength are set at -2.6 dBm and 1543 nm respectively. Moreover, this configuration reveals the highest peak power discrepancy between odd- and evenorder Stokes lines (22.5 dB) in comparison with other configurations with 20 GHz spacing.